Aircast Award for Basic Science - The Effect of Dynamic Changes in ACL Graft Force on Soft Tissue ACL Graft-Tunnel Incorporation. Issue 7 (29th July 2014) - Ma, Richard; Schaer, Michael; Chen, Tina; Sisto, Marco; Voigt, Clifford; Nguyen, Joseph; Ying, Lilly; Deng, Xiang-Hua; Rodeo, Scott A.
Objectives: Anterior cruciate ligament grafts that are placed for reconstruction are subject to complex forces with joint motion. Current "anatomic" ACL reconstructions result in greater in situ graft forces. The biologic effect of changing magnitudes of ACL graft force on graft-tunnel osseointegration is not completely understood. The objective of the present study is to determine the effects of dynamic mechanical ACL graft tension or load on graft-tunnel incorporation. Methods: One hundred male Sprague-Dawley rats underwent unilateral ACL resection followed by reconstruction with a soft tissue autograft. The animals were allocated into one of three groups during surgery: (1) ACL reconstruction followed by limb immobilization for the entire duration of the study, (2) ACL reconstruction with a "high-tension" ACL graft and daily knee motion, or (3) ACL reconstruction with an "isometric" low-tension ACL graft and daily knee motion. ACL graft isometry was assessed intraoperatively. External fixators were used to eliminate graft load during cage activity. Daily knee motion was then started on post-operative day 3 for all animals that were allocated to a knee motion group using a custom computerized knee flexion device. Graft-tunnel healing was assessed at 3 and 6 weeks via biomechanical, micro-CT, and histologic analyses. Biomechanical and micro-CT data was analyzed using ANOVA with significance set at p<0.05. Results: Intraoperative ACL graft force measurements demonstrated two distinct ACL graft curves (high-tension versus isometric ACL graft) were achieved with the two different femoral graft tunnel locations. At 90 degrees of knee flexion, there is a 1.6 fold increase in ACL graft force between a high-tension ACL graft and isometric ACL graft at the time of surgery. High ACL graft force with joint motion appeared to be deleterious to early ACL graft-tunnel incorporation. The load to failure for knees with high-tension ACL grafts (5.50 ± 2.30N) was significantly lower when compared to immobilized (10.90 ± 2.78N, p<0.01) and isometric grafts (9.91 ± 3.36N, p=0.01) at 3 weeks. At 6 weeks, isometric ACL grafts coupled with daily knee motion had greater load to failure than immobilized knees (24.16 ± 5.72N versus 16.56 ± 3.51N, p=0.01). Immobilized and isometric grafts had greater femoral bone volume fraction than knees with high-tension grafts at both 3 and 6 weeks (p<0.01 and p<0.001, respectively). Greater cellularity and collagen gaping were seen in loaded ACL graft (those that underwent motion) versus immobilized grafts, particularly within the tibial tunnel. Higher prevalence of osteoclasts were seen along the graft-tunnel interface in high-tension ACL grafts. Conclusion: There is limited data on how the ACL graft mechanical environment affects its healing. We were able to demonstrate that ACL graft-tunnel incorporation is sensitive to dynamic load from joint motion using a novel small animal model. ACL soft tissue grafts that experience higher in situ force have inferior early biomechanical properties. Maintaining graft isometry allows early joint motion without deleterious biomechanical consequences when compared to immobilized grafts in this animal model. Our findings regarding the effects of graft isometry may not only have clinical implications in terms of post-operative rehabilitation with modern anatomic ACL reconstructions, but it also raises questions regarding existing preclinical ACL healing studies where isometry may not have been considered.